Critical thinking in physics: Momentum critical thinking test for pre-service teacher - Negoro, Ridho Adi; Rusilowati, Ani; Aji, Mahardika Prasetya; Jaafar, Rosly (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2020)
The debate in the making of critical thinking evaluation tests among researchers and practitioners still exists. Problems come from definition and aspects segmentation which represents critical skills to be measured. According to the problems, the specific critical thinking instruments to physics content such as momentum are still hard to find. The instrument of critical thinking can support the learning evaluation to improve the critical power of Pre-Service. This study aims to develop the instrument of momentum critical thinking (MCT) test for Pre-service teachers. The MCT consisted of 8 questions representing 17 objective items. Based on the content validity test, it obtained a total percentage of 81.25% with the eligibility criteria. The reliability test demonstrated by the result of 28 pre-service teacher tests. The MCT instrument which tested was 17 objective items. The reliability test’s results showed Cronbach's alpha value of 0.716 with a high category. Research findings show that the CTM test can be used to measure the CT-specific domain of pre-service teachers in momentum, and relevant material for the consideration of university preparation for pre-service teacher learning in the 21st century